Netrin‐1 Preserves Blood‐Brain Barrier Integrity Through Deleted in Colorectal Cancer/Focal Adhesion Kinase/RhoA Signaling Pathway Following Subarachnoid Hemorrhage in Rats. Issue 5 (19th May 2017) - Xie, Zongyi; Enkhjargal, Budbazar; Reis, Cesar; Huang, Lei; Wan, Weifeng; Tang, Jiping; Cheng, Yuan; Zhang, John H.
Abstract : Background: Netrin‐1 (NTN‐1) has been established to be a novel intrinsic regulator of blood‐brain barrier (BBB) maintenance. This study was carried out to investigate the potential roles of exogenous NTN‐1 in preserving BBB integrity after experimental subarachnoid hemorrhage (SAH) as well as the underlying mechanisms of its protective effects. Methods and Results: A total of 309 male Sprague‐Dawley rats were subjected to an endovascular perforation model of SAH. Recombinant NTN‐1 was administered intravenously 1 hour after SAH induction. NTN‐1 small interfering RNA or Deleted in Colorectal Cancer small interfering RNA was administered intracerebroventricular at 48 hours before SAH. Focal adhesion kinase inhibitor was administered by intraperitoneal injection at 1 hour prior to SAH. Neurological scores, brain water content, BBB permeability, RhoA activity, Western blot, and immunofluorescence staining were evaluated. The expression of endogenous NTN‐1 and its receptor Deleted in Colorectal Cancer were increased after SAH. Administration of exogenous NTN‐1 significantly reduced brain water content and BBB permeability and ameliorated neurological deficits at 24 and 72 hours after SAH. Exogenous NTN‐1 treatment significantly promoted phosphorylated focal adhesion kinase activation and inhibited RhoA activity, as well as upregulated the expression of ZO‐1 and Occludin. Conversely, depletion of endogenous NTN‐1 aggravated BBB breakdown and neurological impairments at 24 hours after SAH. The protective effects of NTN‐1 at 24 hours after SAH were also abolished by pretreatment with Deleted in Colorectal Cancer small interfering RNA and focal adhesion kinase inhibitor. Conclusions: NTN‐1 treatment preserved BBB integrity and improved neurological functions through a Deleted in Colorectal Cancer/focal adhesion kinase/RhoA signaling pathway after SAH. Thus, NTN‐1 may serve as a promising treatment to alleviate early brain injury following SAH.